anonymous
  • anonymous
how do you find intergal of 1/(y^2 -1)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
RadEn
  • RadEn
partial fraction 1/(y^2-1) = A/(y+1) + B/(y-1)
RadEn
  • RadEn
u have to find the values of A and B, first
anonymous
  • anonymous
or trig substitution

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
no sorry that would be a terrible idea
RadEn
  • RadEn
got it ?
RadEn
  • RadEn
1/(y^2-1) = A/(y+1) + B/(y-1) 1/(y^2-1) = ( A(y-1) + B(y+1) )/((y+1)(y-1)) 1/(y^2-1) = ((A+B)y + B-A ) / (y^2-1) A+B = 0 B-A = 1 by using elimination or subtitution, we get B=1/2 and A = -1/2 see ur integral becomes int (-1/2)/(y+1) dy + int(1/2)/(y-1) dy
RadEn
  • RadEn
use integral by u-sub
RadEn
  • RadEn
for int (-1/2)/(y+1) let u = y+1 du = dy it can be : int (-1/2)/u du = -1/2 ln(u)
RadEn
  • RadEn
subtitute back that u = y+1 now, we have int (-1/2)/u du = -1/2 ln(u) = -1/2 ln(y+1)
RadEn
  • RadEn
by same idea to solving int(1/2)/(y-1) dy u = y-1 du = du so, we have int(1/2)/u = 1/2 ln(u) = 1/2 ln(y-1)
RadEn
  • RadEn
finally, we have the answer : -1/2 ln(y+1) + 1/2 ln(y-1) + c
RadEn
  • RadEn
does that make sense ?
anonymous
  • anonymous
perfect sense ty
RadEn
  • RadEn
you're welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.